Arguments against the Christian religion in Amsterdam - Mortera, Saul Levi, 1596?-1660 (Amsterdam studies in the Dutch golden age., 2017)
"This is the first book to offer a translation into English--as well as a critical study--of a Spanish treatise written around 1650 by Rabbi Saul Levi Morteira. Aimed at encouraging the practice of halachic Judaism among the Amsterdam based descendants of conversos, Spanish and Portuguese Jews who had been forced to convert to Christianity, the book stages a dialogue between two conversos that ultimately leads to a vision of a Jewish homeland--an outcome that Morteira thought was only possible thorugh his program for rejudaization."--Back cover.